Mortality of United Kingdom acrylonitrile workers - an extended and updated study - Benn, T.; Osborne, K. (Scandinavian Journal of Work, Environment & Health, 1998)
The mortality experience of 2763 men employed between 1950 and 1978 for at least 1 year at 6 factories involved in the polymerization of acrylonitrile and the spinning of acrylic fiber was followed to the end of 1991. Overall, cancer deaths did not exceed the expected numbers. There were, however, excess cancer deaths among the workers in the jobs more highly exposed to acrylonitrile. The excesses did not reach conventional levels of statistical significance apart from an excess of lung cancer among workers under 45 years of age. Detailed analyses provided no consistent support for a causal association between acrylonitrile exposure and carcinogenesis. The limitations of the study, including a lack of information on smoking habits and very limited estimates of acrylonitrile exposure, need to be borne in mind.
Keywords: acrylic fiber; cancer; occupational cohort; polymerization